Standard Test Methods for Impact Testing of Cast Irons (Metric) (American Society for Testing and Materials, 2006)
These test methods for impact testing cover the details of apparatus, test specimens and procedures for cast iron, including gray iron, white iron, malleable iron, ductile iron, and austempered ductile iron, but not including chilled rolls or rolls with white iron skins.